"Tamed Diseases": The Medical Rationalization of Addiction - Zhengxiao WANG (Yixue yu zhexue)
Academic discussions often focus on issues such as doctor-patient relationship and social control in the medical process, interpreting the development path of medicalization from the perspective of social construction. In the field of addiction research, however, medicine relies on laboratory technology represented by brain imaging science to establish research paradigms by promoting the modeling of knowledge through the logic of excluding contingency factors. Additionally, by rejecting patient subjectivity, medicine constructs patients as standardized entities that align with the principles of knowledge legitimacy. These two ways complement each other, and further promote medicine gradually to pursue more stable and truthful knowledge, ultimately leading to the rationalization of medicine. In this process, medicine's dependence on technology not only reflects the unequal doctor-patient roles emphasized in the social constructivist perspective, but also reflects the "iron cage" of rationality in disease cognition.